Grifola frondosa may play an anti-obesity role by affecting intestinal microbiota to increase the production of short-chain fatty acids - Hu, Ruxiao (Frontiers in Endocrinology, 2023)
Background: Grifola frondosa (G. frondosa) is a fungus with good economic exploitation prospects of food and medicine homologation. This study aims to investigate the effects of G. frondosa powder suspension (GFPS) on the intestinal contents microbiota and the indexes related to oxidative stress and energy metabolism in mice, to provide new ideas for developing G. frondosa weight loss products. Methods: Twenty Kunming mice were randomly divided into control (CC), low-dose GFPS (CL), medium-dose GFPS (CM), and high-dose GFPS (CH) groups. The mice in CL, CM, and CH groups were intragastrically administered with 1.425 g/(kg·d), 2.85 g/(kg·d), and 5.735 g/(kg·d) GFPS, respectively. The mice in CC group were given the same dose of sterile water. After 8 weeks, liver and muscle related oxidative stress and energy metabolism indicators were detected, and the intestinal content microbiota of the mice was detected by 16S rRNA high-throughput sequencing. Results: After eight weeks of GFPS intervention, all mice lost weight. Compared with the CC group, lactate dehydrogenase (LDH) and malondialdehyde (MDA) contents in CL, CM, and CH groups were increased, while Succinate dehydrogenase (SDH) and Superoxide Dismutase (SOD) contents in the liver were decreased. The change trends of LDH and SDH in muscle were consistent with those in the liver. Among the above indexes, the change in CH is the most significant. The Chao1, ACE, Shannon, and Simpson index in CL, CM, and CH groups were increased. In the taxonomic composition, after the intervention with GFPS, the short-chain fatty acid (SCFA)-producing bacteria such as unclassified Muribaculaceae, Alloprevotella, and unclassified Lachnospiraceae increased. In linear discriminant analysis effect size (LEfSe) analysis, the characteristic bacteria in CC, CL, CM, and CH groups showed significant differences. In addition, some characteristic bacteria significantly correlated with related energy metabolism indicators. Conclusion: The preventive effect of G. frondosa on obesity is related to changing the structure of intestinal content microbiota and promoting the growth of SCFAs. While excessive intake of G. frondosa may not be conducive to the antioxidant capacity and energy metabolism.